The influence of the propeller loading on the thrust deduction fraction. Issue 1 (2nd January 2022) - Saettone, Simone; Taskar, Bhushan; Steen, Sverre; Andersen, Poul
ABSTRACT: The estimation of the thrust deduction fraction is generally conducted in ideal weather conditions. However, the presence of waves considerably alters the magnitude of this propulsive coefficient. The increased load of the propeller could be the main cause for the variation of the thrust deduction fraction in realistic operating conditions. In this work, load-varying self-propulsion model-scale numerical simulations in calm water conditions for the same ship speed are performed to investigate the influence of the propeller loading on the thrust deduction fraction. The single screw model-scale KVLCC2 tanker is selected as the case study. The results reveal a non-linear inverse correlation between the thrust deduction fraction and the propeller loading. A comparison with model-testing conducted on the KVLCC2 tanker in regular head waves suggests that the propeller loading is the main factor influencing the magnitude of the thrust deduction fraction in waves for the considered case vessel.